Roles for IFT172 and Primary Cilia in Cell Migration, Cell Division, and Neocortex Development - Pruski, Michal; Hu, Ling; Yang, Cuiping; Wang, Yubing; Zhang, Jin-Bao; Zhang, Lei; Huang, Ying; Rajnicek, Ann M.; St Clair, David; McCaig, Colin D.; Lang, Bing; Ding, Yu-Qiang (Frontiers in Cell and Developmental Biology, 2019)
The cilium of a cell translates varied extracellular cues into intracellular signals that control embryonic development and organ function. The dynamic maintenance of ciliary structure and function requires balanced bidirectional cargo transport involving intraflagellar transport (IFT) complexes. IFT172 is a member of the IFT complex B, and IFT172 mutation is associated with pathologies including short rib thoracic dysplasia, retinitis pigmentosa and Bardet-Biedl syndrome, but how it underpins these conditions is not clear. We used the WIM cell line, derived from embryonic fibroblasts of Wimple mice (carrying homozygous Leu1564Pro mutation in Ift172), to probe roles of Ift172 and primary cilia in cell behavior. WIM cells had ablated cilia and deficiencies in directed migration (electrotaxis), cell proliferation and intracellular signaling. Additionally, WIM cells displayed altered cell cycle progression, with increased numbers of chromatids, highlighting dysfunctional centrosome status. Exposure to a physiological electric field promoted a higher percentage of primary cilia in wild-type cells. Interestingly, in situ hybridization revealed an extensive and dynamic expression profile of Ift172 in both developing and adult mouse cortex. In vivo manipulation of Ift172 expression in germinal regions of embryonic mouse brains perturbed neural progenitor proliferation and radial migration of post-mitotic neurons, revealing a regulatory role of Ift172 in cerebral morphogenesis. Our data suggest that Ift172 regulates a range of fundamental biological processes, highlighting the pivotal roles of the primary cilium in cell physiology and brain development.